KONFLIK PARTAI PERSATUAN PEMBANGUNAN (PPP) TAHUN 2014-2016 - Feri Arawan; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
PPP is a big house for Moslem, but then this political parties with symbolize Ka’bah often attacked of conflict around the secretariat among the conflict between faction on beginning stand, conflict of Djaelani Naro and politicians NU. After reformation PPP obtain the serious problem who influential on gaining vote in General Elections 1999. Declined of gaining vote PPP make the PPP determine coalition on Pilpres 2014. In beginning determine of coalition PPP return obtain conflict, begin with attitude Suryadharma Ali who reputed unilateral by 27 DWP when attend open compaign political parties of Gerindra. Then, the conflict fluctuate when KPK decide SDA as accused of corruption donation of Haji on year 2010-2011 and 2012-2013. PPP doing Mukernas in Bandung and dismissal SDA as chief from position as chief in PPP. However, SDA opposed dismissal herself and claimed Mukernas in Bandung is illegal. Then, SDA dismiss some caretaker daily PPP that is, Romahurmuziy, Emron Pangkapi, Suharso Monoarfa, Lukman Hakim Saifuddin, Reni Marlinawati, Joko Purwanto, Dini Mentari, Emalena Muslim, Aunur, Rusli Effendi, Yusroni Yazid, Hizbiyah Rohim, Siti Maryam, Siti Nurmala, and Mahmud Yunus.The aim of this research is to explain about process of happen the conflict PPP on year 2014-2016. From this research eventually will be seen how about the conflict it be ongoing. The approach theory is used as instrument of analysis conflict PPP on year 2014-2016 is a theory of political parties and conflict. While, the method by using Library Resesarch consider as most important of data aggregate and documentary.Based on the result of research, the conflict internal PPP start from decision SDA as accused case of corruption criminal. The conflict of PPP continued because there is no central figure who regarded by cadre within the solution of problem and solution of the conflict will be done by arbitration method.Keyword : Conflict, Dualism of Leadership, PPP